The Legal-Ethical Risks of Paylater Promotions in Food Purchases: Consumer Protection and Wafā’ bi al-ʿUqūd - Nia Nur Azqia, Ahzun; Huda , Nurul; Al Anang , Arif (Universitas Islam Negeri Alauddin Makassar, 2026)
The development of Buy Now Pay Later (BNPL) services in Indonesia functions not only as a payment method but also as a promotional strategy in the consumption sector. One example is the Rp1 food voucher promotion at Mie Gacoan outlets, which requires the use of YUP PayLater. This study aims to analyze the practice from the perspectives of consumer protection law and the principle of wafā’ bi al-‘uqūd (fulfillment of contracts). The research employs a qualitative method with a juridical-normative and conceptual approach through library research and analysis of documented promotional materials published in online media.The findings reveal two main points. First, the promotional materials prominently display the discount value without explicitly stating that PayLater constitutes a digital financing facility that creates deferred payment obligations. Second, no concise explanation is provided regarding the contractual mechanism, potential additional charges, or consequences of late payment in the promotional media, resulting in an information imbalance between business actors and consumers. This situation indicates that transparency requirements and contractual clarity have not been optimally fulfilled. The study recommends strengthening disclosure standards in promotional practices and enhancing consumer contractual literacy in PayLater transactions.